Prominence and word stress levels in compound words in the Halle orthoepy research - Skoczek, Robert (Papers in Linguistics, 2024)
The article concerns the orthoepic issues regarding accent structures. It turns out to be difficult to determine the prominence of the syllables of compound words in the German Pronunciation Database many times, in which, based on these structures, entries are to be reproduced by high-quality synthesizers in the future. The article examines the issue in terms of the codification of the German pronunciation in Halle.